The Implementation of E-Report Card in the Digital Transformation of Educational Services on the Satisfaction of Parental Involvement of Elementary School Students - Lia Aprianti; Rini Werdiningsih; Emiliana Sri Pudjiarti (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study aims to analyse the impact of e-report card implementation within the framework of digital transformation in educational services on parental satisfaction and involvement at the elementary school level. Employing a narrative literature review, the research synthesised 47 articles published between 2019 and 2025, retrieved from international and national academic databases such as Google Scholar, DOAJ, CORE, the Garuda Portal, and institutional repositories. Thematic analysis generated five core findings. First, e-report cards are identified as a determinant of parental satisfaction, showing a strong positive correlation with improved parental trust and transparency in assessment processes. Second, digital transformation functions as a catalyst that enhances parental engagement, with evidence of up to a threefold increase in participation. Third, the quality of systems and clarity of information play mediating roles, ensuring that digital tools contribute effectively to parental outcomes. Fourth, challenges related to the digital divide and levels of digital literacy moderate the effectiveness of implementation, often influencing disparities in outcomes across different socioeconomic contexts. Finally, the process of adaptation follows a gradual four-stage evolutionary model, highlighting how parents integrate digital platforms over time. Overall, the study confirms a significant positive relationship between e-report card implementation and parental satisfaction and involvement, while also recognising the influence of contextual factors such as infrastructure readiness and socioeconomic diversity. The findings contribute theoretically through the development of the Digital Parental Engagement Model and offer practical insights for formulating educational digitalisation policies that are responsive to district-level stakeholder needs.